Impact of the National Professional Qualification Program (PNQ) on Income: An Econometric Analysis in Piracicaba/SP-Brazil - Diogo Ferraz; Fabíola Cristina Ribeiro de Oliveira (Pesquisa & Debate, 2018)
This paper presents the analysis of the results of the National Program for Professional Qualification - PNQ in Piracicaba/Sao Paulo - Brazil. It analyzed the impact of PNQ on the income of workers. The Theory of Human Capital is presented as a suitable theoretical basis. We used econometric method "diffs-in-diffs", which compares the income of a group of skilled workers with others who did not attend the program. It proved to be rise in income and increased formalization of skilled workers. It was proved the viability of public policy professional qualifications in the municipality. – – Este trabalho apresenta os resultados da análise do Programa Nacional de Qualificaç\~ao Profissional – PNQ em Piracicaba/SP. Analisou-se o impacto do PNQ sobre a renda dos trabalhadores. A Teoria do Capital Humano se apresentou como embasamento teórico adequado, ressaltando a importância do treinamento na vida dos trabalhadores. Utilizou-se método econométrico “diffs-in-diffs”, que compara a renda de um grupo de trabalhadores qualificados com outro que n\~ao frequentou o programa. Comprovou-se elevaç\~ao na renda e aumento da formalizaç\~ao dos trabalhadores qualificados. Destacou-se a importância da participaç\~ao de outros agentes sociais. Ficou comprovada a viabilidade da política pública de qualificaç\~ao profissional no município.
Keywords: I26; I28; 330; Professional qualification; Income; Difference in Differences Method; Econometrics